Kateryna Polishchuk. Volunteer action to the East of Ukraine with friends, 2021 : Kateryna Polishchuk. Volunteer action to the East of Ukraine with friends, 2021 - Polishchuk , Kateryna (Young Scholars Grinchenko – Seton International Journal, 2022)
Kateryna Polishchuk. Volunteer action to the East of Ukraine with friends, 2021